Can straw based enrichment treat tail biting in pigs? - Liston, Abigail (Veterinary Evidence, 2022)
PICO question Can straw based enrichment be used successfully as a treatment intervention to reduce tail biting injuries in weaner to finisher pigs housed in indoor farming systems? Clinical bottom line Category of research question Treatment The number and type of study designs reviewed Three papers were critically reviewed. All three papers answered the PICO question and matched the inclusion criteria for this Knowledge Summary, providing moderate evidence. One non-randomised controlled trial and two randomised controlled trials. Strength of evidence Moderate Outcomes reported Veit et al. (2016) found that straw based enrichment can reduce tail biting, similarly, Larson et al. (2018) found straw based enrichment could reduce tail biting, however, other factors contribute more so to reducing tail biting. Haigh et al. (2019) did not find evidence to suggest straw-based enrichment could reduce tail biting. Triggers for tail biting injuries are multifaceted, therefore enrichment alone will not eliminate pen mate manipulation Conclusion In view of the strength of evidence and the outcomes from the studies the following conclusions have been made; it is expected that these findings provide enough evidence to encourage farmers to introduce novel straw based enrichment as a treatment measure, however it would be most effective if other husbandry factors could be considered in addition How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.